THE COMPARATIVE STUDY OF EFL PRE-SERVICE TEACHERS SELF-EFFICACY BETWEEN PRE-TEACHING PRACTICE AND POST-TEACHING PRATICE - Wanda Siti Nurchaliza; Alfan Zuhairi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
The aim of this study is to compare pre-teaching practice students and post-teaching practice students’ self-efficacy to find out whether enactive mastery does have effect in shaping EFL Pre-service self-efficacy. The ex post facto research design was used which implemented comparative research. The study attempted to analyze the difference between pre-service teacher students’ self-efficacy. The result showed that post-teaching students had highest self-efficacy in students’ engagement, followed by class management, and instructional strategy, while pre-teaching practice students had highest self-efficacy in class management, and followed by students’ engagement and instructional strategy. The result of three dimensions showed that there was significant difference on pre-service teachers’ self-efficacy between pre-teaching practice students and post-teaching practice students, in which post-teaching practice had higher self-efficacy compared to pre-teaching practice.